Millets for little ones: child feeding practices and nutritional profile of millet-based foods in Telangana, India - Shaji, Ilene Maria; Patil, Shreyas; John, Remya Mary; Renjith, Abhirami; Kona, Chandralekha; Reddy, Mounika; Ramaswamy, Gomathi (Frontiers in Nutrition, 2025)
BackgroundMillets are nutrient-dense, climate-resilient grains with the potential to combat child malnutrition. There is limited data available on millet consumption among under-five children and the nutritional quality of millet-based ready-to-eat (RTE) and ready-to-cook (RTC) products available in the market, specifically for under-five children in India.MethodsThe study methodology has two components: (i) A cross-sectional study was conducted in Telangana, India, among 384 mother–child dyads attending a tertiary care hospital. Data on millet-related feeding practices were collected from the mothers through interviews. (ii) Nutrient profiles and labeling details of millet-based RTE and RTC products were assessed by visiting supermarkets, bakeries, and online grocery markets in two districts of Telangana.ResultsWhile 99% of mothers were aware of millets, only 60% included them in their child’s diet at least for 2–3 days a week. Children who consumed millets showed significantly higher height, weight, and MUAC compared to non-millet-consumed children (p < 0.05). Most millet-based RTE and RTC products met energy, protein and iron needs, but had low calcium content as per the estimated average requirement (EAR) for 100 g of the food across age groups. The sodium content of the 20% RTC millet foods was sufficient to fulfill 75% of the recommended daily allowance of children aged 6 months to 6 years. All food product labels had information on ingredients, manufacturing, expiry dates, and lot/ batch numbers. However, there were lacunae in mentioning the additives/food color, suitable age range for consumption, storage conditions and allergen information.ConclusionMothers of under-five children in Telangana India have good knowledge of millets. However, 40% of them did not provide millet to the children regularly. The children who consumed millets had better anthropometric indicators compared to those who did not consume. There is a need to strengthen the food labeling practices on RTC and RTE millet-based foods.